Cost variation analysis of oral anti-diabetic drugs - Mehani, Rekha; Sharma, Parag (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Diabetes Mellitus is a chronic metabolic disorder, one of the major causes of morbidity, mortality and needs lifelong treatment. There are large numbers of oral anti-diabetic drugs available for the treatment of type 2 diabetes mellitus. There are numerous brands available for each of the individual oral anti-diabetic drug. Thus, a study was planned to find out cost variation among different brands of same active oral anti-diabetic drug. Methods: Cost of a particular drug being manufactured by different companies, in the same strength and dosage forms was obtained from the price list provided by the pharmaceutical companies in Current Index of Medical Specialities (CIMS) (October 2017- January 2018). The difference in the maximum and minimum price of the same drug manufactured by different pharmaceutical companies and percentage variation in price was analyzed. Results: Percentage cost variation of the commonly used drugs found was seen highest with Sulfonylureas (Glimepiride - 562%) followed by Metformin (492%) which was followed by Pioglitazone (488%), DPP-4 inhibitor Teneligliptin (231%), α- glucosidase inhibitors (Voglibose 284%), Meglitinides (Repaglinide 0.5mg 154%) and lowest was seen with Repaglinide 2mg (15%). Conclusions: There is very wide cost variation among different brands of the same oral anti-diabetic drugs manufactured in India. The average percentage cost variation of different brands of the same oral anti diabetic drugs manufactured in India is very wide. The appraisal and management of marketing drugs should be directed toward maximizing the benefits of therapy and minimizing negative personal and economic consequences.